PEMBINAAN PENGENALAN BASIC ENGLISH CONVERSATION AT THE AIRPORT KEPADA STAF BANDARA HANG NADIM BATAM - Robby Satria; Nurma Dhona Handayani; Ellbert Hutabri (ASOSIASI IDEBAHASA KEPRI, 2022)
English is an international language which is very important for smooth bilingual interaction. Along with the times, the ability to speak English is required in all aspects of life to develop. One that is experiencing rapid development is the air transportation industry, which has a similar impact on the development of the airport aspect as a facility for providing aircraft transportation services. One of the important airports in the Riau Archipelago is Batam's Hang Nadim Airport. The airport was officially opened to the public on January 1, 1995 under the name